Study of modakaya with special reference to sanjeewanie kameshwari rasayanaya - Sandakelum, H.M.D.S.; Herapathdeniya, S.K.M.K.; Nallaperuma, D.M. (Faculty of Indigenous Medicine, University of Colombo, 2024)
Modaka, a preparation in Ayurveda pharmaceutics involves grinding powdered ingredients with base like bee honey and ghee. This study focuses on Sanjeewanie kameshwari rasayanaya which is renowned for its rejuvenative and aphrodisiac properties among Modaka preparations. Sanjeewanie kameshwari rasayanaya was prepared according to Sri Lankan Ayurveda pharmacopeia following standard operating procedures at the Sanjeewani Ayurveda Drug Company, Embilipitiya. Organoleptic analysis, physico-chemical analysis, total sugars, coloring matter, free fatty-acids and aflatoxins detection, microbiological assessments, heavy metal analysis using microwave digestion and chromatographical studies were performed to determine quality and safety of it. The drug sample and standard raw material mixture were extracted into dichloromethane separately for chromatographical studies and developed chromatograms (Ethyl-acetate: Dicholomethane: Cyclohexane 0.1:3.4:1.5) were visualized under 254nm and 366nm UV light after spraying with Vanillin-sulphate reagent. Physically, Sanjeewanie kameshwari rasayanaya exhibited a loss on drying of 3.6% and total-ash of 2.8%, meeting standard values. Microbiological assessments revealed, aerobic plate count (1.9×104), Escherichia coli (absent), Staphylococcus aureus(<10), yeast and mould count (<100), Salmonella spp. (absent), Pseudomanas aeruginosa (<100) were within acceptable limits. Heavy metals like lead, cadmium, arsenic and mercury, aflatoxin B1, B2, G1, G2 and total aflatoxin and synthetic dyes were not detected in the sample. Total sugar content and free fatty acids were 27.7% and 2.0% respectively. TLC fingerprint profile of the drug sample was comparable in terms of Rf values (0.20, 0.27, 0.39, 0.44, 0.50, 0.58, 0.69, 0.78, 0.89, 0.94) and colors to the profile of standard raw material mixture. In conclusion, Sanjeewanie kameshwari rasayanaya demonstrates its status as a standard drug by meeting established safety and quality standards.
Keywords: Sanjeewanie kameshwari rasayanaya; microbial contamination; TLC